The contribution of M.S. Filonenko to the organization of work the train-service department on the South-Western railways - Rudiuk, M. V. (History of science and technology, 2014)
The contribution of prominent railway engineer M.S. Filonenko to the development organization of railway field operations the train-service department in Russia of the late ХIХ century is reported in the article. The detailed description of the structure of the train-service department on the South-Western railways 1880 –1895, and the changes proposed by M.S. Filonenko to improve it’s functioning.